AUTOMATION AND DIGITALIZATION OF PERSONNEL MANAGEMENT PROCESSES IN THE CIVIL SERVICE - Sopilko, Iryna; Krutas, Vladyslava (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Objective: to study of the transformational processes of human resource management (human resources) in public services, which today have become automated and digitalized. Methods of research: methods of analysis and cognition, the comparative-legal method were used. The constituent methodological framework is a combination of critical, rational and constructive approaches, which allowed us to investigate the legal mechanism of applying the processes of automation and digitalization and provide the author’s definition of an integrated information system of personnel (human resources) management in public service. Results: under the conditions of digitalization of the country, the functioning of a unified database of civil servants and other employees of state agencies will allow to automate (optimize) the processes of human resource management in state agencies and improve procedures for the preparation of decisions on personnel issues, as well as timely and effective monitoring of the performance of state agencies on personnel management issues. The integrated information system of human resource management in the civil service is a single automated database of civil servants and employees of state agencies, which is united with other information state resources and functions through the use of a set of methods and procedures in a certain format in a unified manner to meet the needs of users related to personnel management issues. The implementation and use of protection of information and communication systems that may suffer from cyber-attacks is recommended. Discussion: the study of automation and digitalization processes in the civil service is relevant, because the country’s ability to provide quality services and ensure the interests of citizens depends on its ability and efficiency. The problematic issue is the lack of properly trained civil servants and other employees of government agencies, who would have the appropriate level of knowledge for the implementation of the new information system "HRMIS" and with certain skills of its use and maintenance. The lack of a detailed legal and regulatory framework governing the sphere of implementation of an integrated human resource management system in public authorities also hinders this process.